Patterns of diet‐related practices and symptoms of gastroesophageal reflux among high school students: A cross‐sectional study - Evita Muslima Isnanda Putri; Sri Mulyani; Rahmawati Rahmawati; Indri Dwi Octavia Cahyani (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: GERD is a gastrointestinal motility disorder characterized by the reflux of gastric contents into the esophagus, causing typical symptoms such as heartburn (a burning sensation in the epigastric region), acid regurgitation (a bitter taste in the mouth), nausea, and dysphagia, which can lead to esophageal mucosal damage. Over the long term, it can result in complications like Barrett's esophagus. The prevalence of GERD in Asia was approximately 2.5%-7.8% in 2014, generally lower compared to Western countries. However, recent data indicates an increasing prevalence. Poor dietary patterns, such as irregular eating habits, consuming low-nutrient foods, excessive or insufficient food intake, can elevate gastric acid production and affect an individual's health.Purpose: To determine the relationship between dietary patterns and symptoms of Gastroesophageal Reflux Disease (GERD) among vocational high school students.Method: A quantitative study was applied using correlation analysis with a cross-sectional study approach. The research was conducted at Vocational High School Bojonegoro in January 2023. The study population comprised 305 students in grade 12. The sampling technique employed was purposive sampling, with a sample size of 74 respondents. The measurement tool for dietary pattern variables was the FFQ questionnaire, and GERD symptoms were assessed using the GERD-Q questionnaire. Data analysis techniques included univariate analysis to describe the frequency distribution of each variable and bivariate analysis using the chi-square test to determine the relationship between dietary patterns and GERD symptoms among students.Results: Poor dietary patterns were found to cause GERD in 47 (97.9%) respondents, whereas good dietary patterns significantly minimized GERD; only 1 (2.1%) respondent experienced GERD symptoms in this study. The research resulted a value of ρ = 0.000 < α (0.05), indicating that the ρ value in this study was less than α (0.05) or below 0.05; thus, H0 was rejected. It can be concluded that there is a relationship between dietary patterns and GERD symptoms, with a correlation coefficient value of 0.542 (moderate) and a positive correlation direction.Conclusion: There is a significant relationship between dietary patterns and GERD symptoms. The correlation coefficient analysis also showed a figure of 0.542 (moderate) with a positive correlation direction, indicating that better dietary patterns lead to fewer respondents suffering from GERD.Suggestion: It is advisable for students to avoid consuming spicy foods, fast food, fried food, and high-sugar food or beverages. They should pay more attention to a balanced diet and timely meals. Additionally, the school authorities are encouraged to establish regulations or advisories to cafeteria owners to refrain from providing fast food, nutritionally poor food, carbonated drinks, spicy food, and other items that may contribute to digestive problems among students.